ANALISIS HUKUM IMPLEMENTASI PERPINDAHAN PERWALIAN DALAM PERNIKAHAN - Abd. Aziz Tambunan; Dhiauddin Tanjung (Universitas Islam Sumatera Utara, 2023)
Marriage is a worship that is highly recommended by religious teachings, which aims to continue the existence of the caliph generation on earth. The basis and references regarding marriage have been elaborated in various legal regulations, both fiqh and Indonesian legal regulations. The guardian in a marriage is one of the pillars that must exist in a marriage. This has been regulated by Islamic law including KHI. Even in the Marriage Law, the prerequisites regarding this matter have also been emphasized. Although the existing regulations do not explain in detail the issues of guardianship and transfer related to this problem. Keywords: Implementation, Transfer Of Collateral, Marriage